Current status and prospects of diagnosis and treatment of genetic kidney diseases in Chinese children - SHEN Qian (Zhenduanxue lilun yu shijian)
Genetic kidney diseases refer to a broad category of renal disorders associated with genetic etiologies. They are the leading cause of end-stage kidney disease in children and adolescents，accounting for over 25% of pediatric patients requiring renal replacement therapy. In recent years，advancements in genetic testing technology have significantly improved the diagnostic rates of genetic kidney diseases，while comprehensive clinical evaluation and early screening of high-risk populations are of great diagnostic value. Currently，most genetic kidney diseases lack targeted therapies. Drug treatment prima-rily aims to provide symptomatic support，control proteinuria，and delay kidney function decline. The rapid development of gene therapy technology has brought hope for targeted etiological treatment of genetic kidney diseases. From 2014 to 2020，clinical phenotypes and whole-exome sequencing data from 2 256 pediatric patients with kidney diseases were analyzed to characterize the genetic spectrum of kidney diseases in Chinese children. The clinical diagnoses included steroid-resistant nephrotic syndrome （23.5%），glomerulonephritis （32.2%），CAKUT （21.2%），cystic kidney disease （3.9%），nephrocalcinosis or renal calculus （3.6%），tubulopathies （9.7%），and CKD of unknown etiology （5.8%）. The precision and treatment strategies，established based on the Chinese Children Genetic Kidney Disease Database （CCGKDD），enhance the diagnosis and treatment capabilities for pediatric genetic kidney diseases by focusing on genetic spectrum characterization，exploration of new genes and mechanisms，multi-center clinical research，and full life-cycle management.